Performance of the PV Subsystems in Smart Micro Grid Sumba - Kholid Akhmad; Eka Nurdiana; Nur Aryanto Aryono; Hamzah Hilal (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2017)
Smart Micro Grid (SMG) Sumba is inaugurated in 2012. The SMG consists of sub-system PV of a-Si/μc-Si with capasity 500 kWp, smart generator of 2x135 kVA, VRB of 2x240 kWh, and sub-system control and data communication. The output of the SMG is connected to the grid at 20 kV. Sub-system PV is connected to the 5 unit’s inverter of PV-grid type with each power capacity of 100 kW.At the beginning of operation, sub-system PV is operated at maximum level (100%). Electrical power is about 400 kW-500 kW supplied to the grid in clear daytime continuously from 10:00-15:00. When it is cloudy, the electrical energy supplied to the grid varies according to fluctuations in the intensity of light on the surface of PV arrays. Base load during the daytime in Southwest Sumba Regency at the time is about 1.5 MW, meaning that the contribution of electric energy of PV array is almost 30%. The change of cloud abruptly causes the output of PV to drop significantly, which could lead to black out at the local grid because the generators of PLN are not able to cover the power loss immediately. These restrictions result in Sumba SMG can not be operated optimally. Local power company can not tolerate frequent black outs due to the fluctuating of power injection from PV array.Over time some of the components of VRB are damaged so that the VRB is not enabled. Then, the SMG is applied to the extent of PV-grid connections, with the restriction of the power output of PV array at a rate of 30%, or power supplies 150 kW continuously during the daytime. As the SMG has been operated for about four years, the performance of the PV array has degraded about 20%-30%. The changes evidenced in the form of an electric current-voltage curves of PV module are measured by Sun-Simulator.In this paper, it is also discussed general information about the SMG system built in Southwest Sumba Regency, and specifically reviewing the performance of the sub-systems PV since it was built until now.